Combined Multidimensional Microscopy as a Histopathology Imaging Tool. Issue 2 (9th July 2016) - Shami, Gerald J.; Cheng, Delfine; Braet, Filip
Abstract : Herein, we present a highly versatile bioimaging workflow for the multidimensional imaging of biological structures across vastly different length scales. Such an approach allows for the optimised preparation of samples in one go for consecutive X‐ray micro‐computed tomography, bright‐field light microscopy and backscattered scanning electron microscopy, thus, facilitating the disclosure of combined structural information ranging from the gross tissue or cellular level, down to the nanometre scale. In this current study, we characterize various aspects of the hepatic vasculature, ranging from such large vessels as branches of the hepatic portal vein and hepatic artery, down to the smallest sinusoidal capillaries. By employing high‐resolution backscattered scanning electron microscopy, we were able to further characterize the subcellular features of a range of hepatic sinusoidal cells including, liver sinusoidal endothelial cells, pit cells and Kupffer cells. Above all, we demonstrate the capabilities of a specimen manipulation workflow that can be applied and adapted to a plethora of functional and structural investigations and experimental models. Such an approach harnesses the fundamental advantages inherent to the various imaging modalities presented herein, and when combined, offers information not currently available by any single imaging platform. J. Cell. Physiol. 232: 249–256, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Herein, we present a highly versatile bioimaging workflow for the multidimensional imaging of biological structures across vastly different length scales, utilising X‐ray micro‐computed tomography, bright‐field light microscopy and backscattered scanning electron microscopy on the same sample. By harnessing such an approach, we characterise various features of the hepatic microvascular network ranging from the tissue level down to the nanometre scale. Above all, we demonstrate the capabilities of a specimen manipulation workflow that can be applied and adapted to a plethora of functional and structural investigations, and experimental models.